2013
DOI: 10.3111/13696998.2013.778270
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and cost of systemic lupus erythematosus in a US managed care health plan

Abstract: SLE is associated with high levels of healthcare utilization and costs in a managed care health plan. Inpatient hospital stays were the primary medical cost drivers, followed by physician office visits and outpatient hospital visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
148
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(168 citation statements)
references
References 37 publications
8
148
4
1
Order By: Relevance
“…Among GC users, more than half were prescribed with at least 60 days of therapy. In particular, close to two-thirds of the patients using GCs for more than 60 days were prescribed with a daily prednisone or equivalent dose of .7.5 mg. Our study reported the average annual total cost of all SLE patients to be $21,535, which was similar to what has been reported previously for the commercially insured population ($15,000-21,000) (5,23,24). We further found that higher GC doses were associated with higher health care utilization and costs.…”
Section: Discussionsupporting
confidence: 89%
“…Among GC users, more than half were prescribed with at least 60 days of therapy. In particular, close to two-thirds of the patients using GCs for more than 60 days were prescribed with a daily prednisone or equivalent dose of .7.5 mg. Our study reported the average annual total cost of all SLE patients to be $21,535, which was similar to what has been reported previously for the commercially insured population ($15,000-21,000) (5,23,24). We further found that higher GC doses were associated with higher health care utilization and costs.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have demonstrated that both are higher in patients with SLE compared to controls (5,10,19,20). The current study confirms this observation, but also demonstrates a consistent change in the pattern of utilization over the 13 years of observation.…”
Section: Discussionsupporting
confidence: 89%
“…Studies of health care utilization have consistently found that it is higher in SLE patients than in comparator groups of patients (4,5,10,16). Utilization may be influenced by a variety of factors, including disease severity (17) (higher in lupus nephritis [8,16] and neuropsychiatric lupus [11,16]), race and ethnicity (lower in Hispanics [18]), and the type of health care delivery (higher in the fee-for-service system [3]).…”
Section: Discussionmentioning
confidence: 99%
“…13,819 Annual costs associated with SLE are estimated to be $10,000–50,000 more than those for patients without SLE, with severe flares and more major organ involvement incurring the highest costs. 2040 Major cost drivers include areas where AAs with lupus are disproportionately represented, such as inpatient hospitalizations, 36,41,42 long disease duration, high disease activity and organ damage, poor physical and mental health and low education and employment levels.…”
Section: Introductionmentioning
confidence: 99%